2022 IEEE Workshop on Complexity in Engineering (COMPENG) 2022
DOI: 10.1109/compeng50184.2022.9905448
|View full text |Cite
|
Sign up to set email alerts
|

Functional electrical stimulation driven by a brain–computer interface in acute and subacute stroke patients impacts beta power and long-range temporal correlation

Abstract: Functional electrical stimulation (FES) is a standard rehabilitation approach applied by therapists to aid motor recovery in a paretic limb post-stroke. Information pertaining to the timing of a movement attempt can be obtained from changes in the power of oscillatory electrophysiological activity in motor cortical regions, derived from scalp electroencephalographic (EEG) recordings. The use of a brain-computer interface (BCI), to enable delivery of FES within a tight temporal window with a movement attempt de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The improvements following BCI-FES in patients early post-stroke in these studies are consistent with our findings. Moreover, our preliminary analyses indicated that the increases in FMA and in beta desynchronization, as well as the reduction in beta LRTC, were observable in all four BCI group patients individually 40 . The small numbers of patients included at an early stage post-stroke highlights the importance of meta-analyses combining the findings from different studies.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The improvements following BCI-FES in patients early post-stroke in these studies are consistent with our findings. Moreover, our preliminary analyses indicated that the increases in FMA and in beta desynchronization, as well as the reduction in beta LRTC, were observable in all four BCI group patients individually 40 . The small numbers of patients included at an early stage post-stroke highlights the importance of meta-analyses combining the findings from different studies.…”
Section: Discussionmentioning
confidence: 72%
“…The improvements following BCI-FES in patients early post-stroke in these studies are consistent with our findings. Moreover, our preliminary analyses indicated that the increases in FMA and in beta desynchronization, as well as the reduction in beta LRTC, were observable in all four BCI-FES group patients individually 41 .…”
Section: Discussionmentioning
confidence: 73%